DSL-003 Automation of Drug Distribution: Impact on Error Rate and Distribution Speed. (12th March 2013) - François, O; Carrez, L; Gschwind, L; Cingria, L; Vernaz-Hegi, N; Bonnabry, P
Abstract : Background: Human reliability is limited and information technology has the potential to improve the safety of the medication process. In July 2011, a robot (ROWA/ARX) was implemented in our hospital pharmacy to reduce error rates and improve the efficiency of our global drug distribution. Purpose: To evaluate the impact of this automation on distribution errors and workload efficiency. Materials and Methods: Approximately 52% of the dispensary stock (1126 articles, 50, 000 boxes) is managed by the robot. Distribution errors: content accuracy of random orders was verified before and after the implementation of the robot. Errors were classified in three categories: wrong drug, missing drug/quantity or additional quantity. Workload efficiency: time to prepare a sequence of orders manually or with the robot was measured. Results: Manual dispensing error rate was 0.93% (n = 5805 ordered lines; wrong drug: 0.36%, missing drug/quantity: 0.31%, additional quantity: 0.26%). By decreasing this error rate to 0.27% (n = 5840; only conveyor errors leading to missing drug/quantity and additional quantity), the automation avoided more than 4500 errors each year. With the distribution of 880 boxes of drugs/hour (reduced to 630 when the automated 'Pro-log' filling system was working simultaneously), the robot significantly increased the distribution speed in comparison with the manual picking (303 boxes/hour). Conclusions: This reorganisation contributed to safer and more efficient distribution of drugs. No more incorrect picking of medicines occurred thanks to the high reliability of the robot. Remaining errors could still be reduced by improving the conveyor software. With one single person operating the robot, 2 full-time equivalents were saved, leading to an estimated return on investment in 4.5 years. For medicines remaining outside the robot (i.e. controlled drugs, cold chain drugs or those with an unusual size, shape or weight), a scanning system will be introduced and evaluated by the same protocol. No conflict of interest.